HUBUNGAN ANTARA PENDAPATAN, DAYA SAING DAN PEMBANGUNAN MANUSIA DI ASIA TENGGARA - Noor Zuhdiyaty (Quantitative Economics Journal, 2017)
Revenue, competitiveness and human development are important in supporting a country's economic development. This study aims to examine the relationship between income, competitiveness and human development in Southeast Asia during the period of five years from 2010-2014. This research uses quantitative approach with correlation test. This study was conducted on 8 (eight) countries in Southeast Asia. The results show that there is am relationship between income, competitiveness and human development, where competitiveness and human development have a strong relationship that is very strong compared to others.